PERLINDUNGAN HUKUM TERHADAP ORANG DENGAN GANGGUAN JIWA YANG TERLANTAR DI RUMAH SINGGAH - Della Syahbana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
That the legal protection for the handling of people with neglected mental disorders is not yet maximized to get a sense of security to be returned to the family and community environment after receiving health rehabilitation treatment at the Shelter and being declared cured or healthy to carry out their social functions, which they should get in order to achieve optimal mental health. The research carried out in this thesis research is normative legal research, where research examines from the point of view of legal science in depth the established norms which are then supported by additional data in the field. Legal protection for people with mental disorders who are abandoned in halfway houses is essentially everyone has the right to get legal protection. This is stated in Article 28 D paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states that everyone has the right to recognition, guarantee, protection and fair legal certainty and equal treatment before the law. Actions in handling people with neglected mental disorders that are carried out in handling people with abandoned souls carried out by the Social Service are sent to the social rehabilitation center. For Satpol PP, the action is to bring order to the streets and say that people with mental disorders are displaced by the Social Service program. This means that there is no unified action between institutions in handling people with neglected mental disorders.